Cover Image, Volume 14, Issue 2. Issue 2 (22nd May 2020) - Unknown
Abstract: On the cover : Dr. Robert Bowden with stem rust resistant wheat germplasm on left, susceptible recurrent parent on right. See M.J. Guttieri et al., "Registration of hard white winter wheat germplasms KS14U6380R5, KS16U6380R10, and KS16U6380R11 with adult plant resistance to stem rust, " https://doi.org/10.1002/plr2.20004 . Photo by Mary Guttieri.